Environmental Protection and Sustainable Development in Rural Tourism: Implications for Promoting Eco-Friendly Practices in Sports and Recreation - Hanteng Li; Yun Qin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study explores the intersection of environmental protection and sustainable economic development in the context of China's rural tourism, with particular attention to its implications for sports and recreational activities in rural areas. Rural tourism, characterized by abundant natural and cultural resources, has the potential to drive rural economic growth and foster community development. However, without proper ecological management, the rapid depletion of tourism resources and damage to natural environments can hinder the long-term viability of these initiatives, negatively impacting both the local economy and opportunities for outdoor sports and recreation. To ensure the sustainable development of rural tourism, it is essential to adopt strategies that balance the utilization and preservation of tourism resources. This involves responsibly developing rural tourism assets while promoting eco-friendly practices that align with the principles of sustainable development. By integrating environmental, economic, and social benefits, these efforts can create harmonious environments that not only support rural economic growth but also enhance opportunities for eco-tourism, outdoor sports, and recreational activities, ultimately fostering a healthier, more sustainable rural lifestyle.